2019
DOI: 10.1016/j.brs.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility in TMS–EEG studies: A call for data sharing, standard procedures and effective experimental control

Abstract: A recent study by Conde, Tomasevic et al. (2019) [1] puts a spotlight on the subtleties of experimental design and analysis of studies involving TMS-evoked EEG potentials (TEPs), specifically focusing on the challenge of disentangling genuine cortical responses to TMS from those resulting from concomitant sensory activation. This is a relevant topic that the TMSeEEG community has previously identified [2] and addressed with different strategies [3e6]. Based on the similarity of the evoked EEG responses they ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 22 publications
7
96
0
Order By: Relevance
“…Furthermore, selecting an adequate stimulation intensity is important for optimising signal-to-noise ratios of early TEP peaks. While we did use anatomical MRI scans to individualise coil placement and observed differences in the scalp topography and source localisation of the early TEP peaks between stimulation sites, we did not check TEP amplitudes online to optimise stimulation intensity and minimise muscle artifact, a method which has recently been advocated to improve signal-to-noise in TMS-EEG recordings 11 . As a result, the early TEP peaks in this study are smaller than those observed by other groups stimulating similar regions 6 .…”
Section: Effects Of Dextromethorphan On Resting Oscillations Sub-anamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, selecting an adequate stimulation intensity is important for optimising signal-to-noise ratios of early TEP peaks. While we did use anatomical MRI scans to individualise coil placement and observed differences in the scalp topography and source localisation of the early TEP peaks between stimulation sites, we did not check TEP amplitudes online to optimise stimulation intensity and minimise muscle artifact, a method which has recently been advocated to improve signal-to-noise in TMS-EEG recordings 11 . As a result, the early TEP peaks in this study are smaller than those observed by other groups stimulating similar regions 6 .…”
Section: Effects Of Dextromethorphan On Resting Oscillations Sub-anamentioning
confidence: 99%
“…However, several recent studies have shown that residual auditory and somatosensory activity resulting from the TMS pulse also contributes to TEPs under certain circumstances despite experimental measures designed to minimise sensory inputs such as auditory masking and foam padding 9,10 . Such findings highlight the need for careful experimental set-up 11 and control conditions 12 in TMS-EEG studies. In support of the excitation/inhibition hypothesis, pharmacological agonists of inhibitory neurotransmission mediated by fast activating γ-aminobutyric acid (GABA)-A receptors given at sub-anaesthetic doses increase the amplitude of early TEPs (e.g.…”
mentioning
confidence: 93%
“…Specifically, sham TMS elicited EEG potentials that were correlated highly with those by real TMS, despite the use of sophisticated procedures to attenuate the somatosensory and auditory confounds. In rebuttal of this publication, it was suggested that insufficient TMS intensity and incomplete auditory masking may explain the sensory-dominant evoked potentials in the experiment[4]. Nonetheless, residual auditory input is unavoidable in TMS studies[5] because of air and bone conduction from the TMS clicking sound[6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the PCI measure has shown similar values in the dreaming state, when one is presumably unconscious of the TMS stimulations, as in the awake state (Casarotto et al, 2016) . Therefore, it seems improbable that attention towards sensory aspects of TMS stimulation affects PCI, when the TMS-EEG procedure is properly executed (Belardinelli et al, 2019) . However, there is an alternative hypothesis: the observed difference in response to auditory pattern irregularities (P3b) might not only be modulated by attentional focus but also by the cognitive load and the use of attentional resources demanded by the task itself.…”
Section: Introductionmentioning
confidence: 99%